Streptococcus pseudoporcinus: Case Reports and Review of the Literature - Shanza Khan; Ting Ting Wong; Nishant Prasad; Benjamin Lee; Carl Urban; Sorana Segal-Maurer; Glenn Turett (Case Reports in Infectious Diseases)
Streptococcus pseudoporcinus is a beta-hemolytic Gram-positive, catalase-negative, nonmotile coccus arranged in short chains, usually found in the female genitourinary tract and differentiated from Streptococcus porcinus in 2006. Only two human infections associated with this organism have been reported to date: one in a patient with a first digit wound infection and another with lower extremity cellulitis. We describe two novel cases of Streptococcus pseudoporcinus causing endocarditis in one and pneumonia with empyema in another, illustrating the potential of these bacteria to cause severe invasive and life-threatening disease.